Analysis of dies material strength in the blade screw conveyor bending process - Muhammad Rizky Imaduddin; Muhamad Fitri (JTTM : Jurnal Terapan Teknik Mesin, 2025)
Screw conveyor is one of material transport equipment in transport bulk materials. When damage will affect the next stage of the production process, a solution in the form of a tool is needed that shortens the fabrication process time of Screw Conveyor, utilizing the pressure from hydraulic cylinder ex excavator against die as the base. To ensure that the tool is able to work optimally with the load received from the hydraulic cylinder pressure 100 tons and upper die 60.28 kg, it is necessary to carry out research using the Finite Element Analysis method of Solidworks Simulation software on material strength of screw conveyor blade bending dies from parameters safety factor and yield strength of Von Misses method with material used is ASTM A36. This research is concluded that strength of die bending blade screw conveyor material which has been made with wall thickness 8 mm meets the requirements with load 981591.347 N, has a maximum stress value using the Von Misses yield strength method of 59 N/mm2 in Solidworks simulation and 48.959 N/mm2 in manual calculations, this value is lower than maximum allowable stress 83.333 N/mm2, maximum displacement value is 0.300 mm, 8 mm wall configuration meets the requirements because it has value 0.108 mm in Solidworks simulation and 0.098 mm in manual calculation. Safety factor value obtained is 4.086, which meets the requirements 3. So that from this research it can be ascertained the ability of the die when given a load of 100 tons during the bending process